Cell-Free Synthesis of a Functional Membrane Transporter into a Tethered Bilayer Lipid Membrane - Zieleniecki, Julius L (Langmuir : the ACS journal of surfaces and colloids, 2016)
Eukaryotic cell-free synthesis was used to incorporate the large and complex multispan plant membrane transporter Bot1 in a functional form into a tethered bilayer lipid membrane. The electrical properties of the protein-functionalized tethered bilayer were measured using electrochemical impedance spectroscopy and revealed a pH-dependent transport of borate ions through the protein. The efficacy of the protein synthesis has been evaluated using immunoblot analysis